Desa dan Manusia Pembangunan: Hambatan dan Dorongan Manusia Desa Sebagai Manusia Pembangunan Berbasis Teknologi Informasi dan Komunikasi di Marihat Dolok - Yosi Irawelda Saragih; Ester Adelyn Lumbanraja; Tasya Isnani Tan; Putri Khairunissa; Widya Maya Damanik; Rafael Eka Josua Siregar; Romario Frans Deonicio Purba; Manres Maruli Nababan; Dian G. Purba Tambak (Pusat Riset dan Inovasi Nasional, 2024)
The increasingly rapid development of information and communication technology (ICT) in an effort to make services more effective for the community must be carried out at the village level. Apart from being able to improve services, the existence of ICT is also useful in processing data which can be used for development planning, supporting decision making and many other benefits. The aim of this study is to identify readiness for ICT application from the aspects of human resources, facilities and infrastructure, institutions and budget and to assess the services through IT that have been provided. The method used is a descriptive method with the research location in Marihat Dolok village in Simalungun Regency. The results of the research findings are the limited number of human resources who master ICT, the network is not evenly distributed, institutional needs are met and there is budget support from authorized institutions and the information system has not accommodated all service needs and has not been implemented in all villages.